Potential Disease-Modifying Effects of Lithium Carbonate in Niemann-Pick Disease, Type C1 - Han, Shiqian; Zhang, Huiwen; Yi, Mengni; Liu, Xiaoqing; Maegawa, Gustavo H. B.; Zou, Yunding; Wang, Qijun; Wu, Dianqing; Ye, Zhijia (Frontiers in Pharmacology, 2021)
Background: Niemann-Pick disease type C1 (NP-C1) is a rare, autosomal-recessive neurodegenerative disorder with no US Food and Drug Administration (FDA)-approved drug. Lithium has been shown to have considerable neuroprotective effects for neurological disorders such as bipolar disorder, Alzheimer’s disease and stroke and has been tested in many clinical trials. However, the pharmacological effect of lithium on NP-C1 neurodegenerative processes has not been investigated. The aim of this study was to provide an initial evaluation of the safety and feasibility of lithium carbonate in patients with NP-C1. Methods: A total of 13 patients diagnosed with NP-C1 who met the inclusion criteria received lithium orally at doses of 300, 600, 900, or 1,200 mg daily. The dose was reduced based on tolerance or safety observations. Plasma 7-ketocholesterol (7-KC), an emerging biomarker of NP-C1, was the primary endpoint. Secondary endpoints included NPC Neurological Severity Scores (NNSS) and safety. Results: Of the 13 patients with NP-C1 (12-33 years) enrolled, 3 withdrew (discontinuation of follow-up outpatient visits). The last observed post-treatment values of 7-KC concentrations (128 ng/ml, SEM 20) were significantly lower than pretreatment baselines values (185 ng/ml, SEM 29; p=0.001). The mean NNSS was improved after lithium treatment at 12 months (p=0.005). Improvement in swallowing capacity was observed in treated patients (p=0.014). No serious adverse events were recorded in the patients receiving lithium. Conclusion: Lithium is a potential therapeutic option for NP-C1 patients. Larger randomized and double-blind clinical trials are needed to further support this finding. Clinical Trial Registration: ClinicalTrials.gov, NCT03201627.